Taxonomic notes on Aristolochia dilatata Brown from India: Lectotypification and a new synonym - Do, Truong Van; Neinhuis, Christoph; Wanke, Stefan (Bangladesh Journal of Botany, 2018)
Aristolochia gourigangaica Nair is proposed here as a synonym of Aristolochia dilatata Brown. Furthermore, the lectotype of Aristolochia dilatata is designated. Its relationship with Aristolochia punjabensis is also discussed.